PENGEMBANGAN MEDIA TRANSFORMASI GEOMETRI UNTUK PEMBELAJARAN MATEMATIKA DALAM MENGENAL SIMBOL GEOMETRI DI KELOMPOK A RA AL-AZHAR DAMPIT MALANG - Korini, Rani Asen; Sari, Ratih Permata (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2024)
PProduct development is made using interactive video techniques with animated nuances and mathematical concept forms. The purpose of the study is to describe the form of the product made, analyze the content of the breadth of material in the product, and the results of the development of the Geometric Transformation animation video in learning materials to recognize geometric symbols at RA Al-Azhar Dampit-Malang. Using the research and development (R&D) method, and using the development stage of the Borg & Gall research model. The results of the study utilize the Canva Pro application for visual design and Capcut for adding voice overs and backsound in the manufacturing process. Innovation in children's mathematics learning using the Geometric Transformation media is found in learning activities using mathematical games that contain children's mathematics indicators related to the classification of geometric symbols and number operations. Media experts get 97.5%. The results of material experts I get 94%, the results of material experts II get 100%. The results of small group trials get 64%, the results of large group trials get 80%. From the results of these studies, the Geometric Transformation media is a media that has innovation and creativity, so it is worthy of being used as a mathematics learning media for early childhood.